2016
DOI: 10.1111/jcmm.12846
|View full text |Cite
|
Sign up to set email alerts
|

Potentially functional polymorphisms in the LIN28B gene contribute to neuroblastoma susceptibility in Chinese children

Abstract: Neuroblastoma is the most commonly diagnosed solid tumour outside the central nervous system in children. However, genetic factors underlying neuroblastoma remain largely unclear. Previous genome‐wide association study indicated that lin‐28 homolog B (LIN28B) might play an important role in the development of neuroblastoma and also contributed to its poor overall survival. With the purpose to evaluate the association between LIN28B gene polymorphisms and neuroblastoma susceptibility in Southern Chinese populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 47 publications
(68 reference statements)
0
31
0
Order By: Relevance
“…Meanwhile, this variant was also found to be associated with the risk and survival of cancers, such as Wilms tumor [22], neuroblastoma [23] and epithelial ovarian cancer [38]. Previous data also showed that LIN28B rs221634 A>T, rs221635 T>C, and rs9404590 T>G were related to the susceptibility to Wilms tumor [22] and neuroblastoma [23].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Meanwhile, this variant was also found to be associated with the risk and survival of cancers, such as Wilms tumor [22], neuroblastoma [23] and epithelial ovarian cancer [38]. Previous data also showed that LIN28B rs221634 A>T, rs221635 T>C, and rs9404590 T>G were related to the susceptibility to Wilms tumor [22] and neuroblastoma [23].…”
Section: Discussionmentioning
confidence: 93%
“…For example, LIN28B rs314276 C>A polymorphism has been shown to associate with reproductive timing [33,34], central precocious puberty [35], the linkage between puberty timing and adult disease [36], and the finger-length ratio [37]. Meanwhile, this variant was also found to be associated with the risk and survival of cancers, such as Wilms tumor [22], neuroblastoma [23] and epithelial ovarian cancer [38]. Previous data also showed that LIN28B rs221634 A>T, rs221635 T>C, and rs9404590 T>G were related to the susceptibility to Wilms tumor [22] and neuroblastoma [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A TIANamp Blood DNA Kit (Centrifugal column, Tiangen) was used to extract DNA from the blood samples according to the manufacturer's instructions . TaqMan real‐time PCR assays were set up in 384‐well plates containing positive and negative samples and were carried out in an ABI Q6 system (Applied Biosystems) to genotype the miRNA‐149 rs2292832 T>C polymorphism …”
Section: Methodsmentioning
confidence: 99%